Exploring Medical Students’ Rural Intention on Course Entry - McNaught, Keith; Rhoding, Colette (Australian and International Journal of Rural Education, 2023)
Understanding the rural intentions of medical students has the potential to improve the effective allocation of rural clinical placements, the demand for which regularly exceeds availability. Longitudinal studies on students’ rural intentions have been published but a refined understanding of the spectrum of intentions is absent in the literature. To fully understand students’ rural intentions, and the factors influencing those intentions, comprehensive research, at all stages of a student’s academic career, is required. The project used for this article, identifies a group with neutral intention and explores the influence of a range of demographic factors and variety of rural experience for their potential to move students towards high rural intention. The study also identifies trends in student perceptions of potential locations for rural practice in Western Australia. This more detailed approach is offered as a basis for a future model to inform the allocation of scarce rural placement opportunities, known to be significant in converting rural intention into practice. The project responds to increasingly frequent calls for changes to policy and practice regarding the allocation of rural clinical placements to better realise their value in improving the maldistribution of Australia’s medical workforce. The study suggests that a greater range of indicators, beyond being of rural origin, can lead to neutral or high rural intention. The results of this study suggest a model that incorporates these additional elements and tracks their development over time would be a valuable component in initiatives aimed at building positive rural intention.